Hubungan Kebiasaan Minum Air Rebusan Kayu Secang Dengan Kebugaran Petani Di Desa Aralle Kecamatan Kohu - Andi Amin Nur; Yusriani; Andi Nurlinda (Journal Prima Health Science, 2020)
Secang (Caesalpinia sappan L.) is a plant that has long been widely used as traditional medicine. The existence of Brazillian and brazilein compounds gives a specific characteristic of cup wood, brownish-red color (Dyvta et al., 2013). Cup wood is a plant that is widely used as traditional medicine. The empirical timber is known to have much healing efficacy and is often consumed by the public as a health drink. Use of cup timber as medicinal herbs, among others, to facilitate blood circulation, drug diarrhea, tuberculosis, antiseptic, anti-inflammatory, and antidote poison (Zerrudo, 1999). This research is forced to know the habit relation drink water stew Secang wood with Farmer's Fitness in village Aralle Sub District Kahu Bone year 2019. This type of research is a quantitative descriptive with the Cross-Sectional Study approach. A population is a research object amounting to 405 patriarchs who are as farmers while the sample used to obtain information data amounted to 94 people. The results are obtained that farmers who often drink the water stew Cup wood have a good level of fitness (category fit and very fit) with a distribution of 62.8%. Once a farmer who occasionally consumes cup wood stew only has a moderate level of fitness (category is very misfit and not fit) with a distribution of 13.8%, with a significant rate of P-V = 0.000. The conclusion of this research is the habit of farmers in Aralle Village to drink secang boiled water more often, 80 people (85.1%), and sometimes 14 people (14.9%). Meanwhile, there is no such thing as (0). Farmers who have very good fitness are 60 people (63.8%), and 34 people are good (36.2).